A single parameter to evaluate stress state in rail head for rolling contact fatigue analysis. (7th February 2014) - Pun, C. L.; Kan, Q.; Mutton, P. J.; Kang, G.; Yan, W.
ABSTRACT Based on the Smith‐Watson‐Topper (SWT) method, a phenomenological approach for multiaxial fatigue analysis, the maximum SWT parameter is proposed as a single parameter to evaluate the stress state in the rail head for assessing the fatigue integrity of the structure. A numerical procedure to calculate the maximum SWT parameter from a finite element analysis is presented and applied in a case study, where the stress and strain fields due to wheel/rail rolling contact are obtained from a three‐dimensional finite element simulation with the steady‐state transport analysis technique. The capability of the SWT method to predict fatigue crack initiation in the rail head is confirmed in the case study. Analogous to von Mises stress for strength analysis, the maximum SWT parameter can be applied to evaluate the fatigue loading state not only in rail head due to rolling contact fatigue but also in a generic structure subjected to a cyclic loading.